2004
DOI: 10.1165/rcmb.2003-0212oc
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Myosin Phosphatase and Ca2+-Uptake Mediate Adrenergic Relaxation of Airway Smooth Muscle

Abstract: We examined the mechanisms underlying relaxations evoked by isoproterenol (Iso) in isolated porcine, bovine, or human tracheal and bronchial tissues (TSM and BSM, respectively). Iso had little effect against contractions evoked by high KCl, indicating that it does not directly suppress voltage-dependent Ca(2+)-influx nor directly inhibit myosin light chain kinase. Furthermore, Iso was equally potent against carbachol (CCh) contractions in the presence versus absence of nifedipine (10(-6) M), establishing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 28 publications
2
35
1
Order By: Relevance
“…The current authors have previously shown that Rho/ROCK activities are in part Ca 2+ dependent [28,40], and b-agonists and NO are known to decrease intracellular calcium levels in airway smooth muscle; however, the present study did not control for changes in intracellular calcium. Future studies of the mechanisms by which b-adrenoceptors couple to the Rho/ROCK signalling pathway will require a careful pharmacological dissection using agents that abrogate one or another of the excitation-contraction coupling pathways.…”
Section: Reversal Of Cholinergically Evoked Responsescontrasting
confidence: 56%
See 1 more Smart Citation
“…The current authors have previously shown that Rho/ROCK activities are in part Ca 2+ dependent [28,40], and b-agonists and NO are known to decrease intracellular calcium levels in airway smooth muscle; however, the present study did not control for changes in intracellular calcium. Future studies of the mechanisms by which b-adrenoceptors couple to the Rho/ROCK signalling pathway will require a careful pharmacological dissection using agents that abrogate one or another of the excitation-contraction coupling pathways.…”
Section: Reversal Of Cholinergically Evoked Responsescontrasting
confidence: 56%
“…Generally speaking, bronchodilators trigger signalling events opposite to those summarised above, including stimulation of the enzymatic activities of adenylate cyclase/protein kinase (PK)A (b-agonists) or of guanylate cyclase/PKG (NO), Ca 2+ uptake and Ca 2+ extrusion, membrane hyperpolarisation, inhibition of MLCK and stimulation of MLCP [7,10,[26][27][28][29]. Interestingly, some of these effects depend upon whether cholinergic stimulation precedes b-adrenoceptor stimulation, or vice versa [7,26,27].…”
mentioning
confidence: 99%
“…PDE4 is shown to be the major PDE subtype in human ASM cells (36). It hydrolyzes cAMP, which is known to activate protein kinase A (PKA)-and exchange protein directly activated by cAMP (Epac)-dependent pathways to regulate ASM functions, such as inhibition of ASM cell proliferation and airway constriction (37)(38)(39). The dramatic increase in pde4 d expression in lungs of HDM-challenged mice, therefore, could cause a significant reduction in cAMP and enhance airway reactivity and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…4) [70]. With respect to ASM relaxation, there are data to suggest that b-adrenoceptor agonists may activate MLCP and that this may play an important role in reducing tone [71]. Moreover, MLCP can also be activated by the cyclic guanosine monophosphate (cGMP)/cGMP-dependent PKG pathway.…”
Section: Adrenoceptors In the Lungmentioning
confidence: 99%